The Impact of Animal Flesh Consumption on Human Genetics - Vaishnavi H. Mishra; Yugeshwari R Tiwade; Obaid Noman (Advances in Human Biology)
The animal flesh has been consumed for millions of years by humans. Although the attention has been increased in recent years on its effect on human genetics, exploring the complex interplay between animal flesh consumption and human genetics sheds light on both potential benefits and risks associated with dietary choices.